2011
DOI: 10.1016/j.bbrc.2011.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Kupffer cell α2A-Adrenoceptors and downregulation of MKP-1 mediate hepatic injury in chronic alcohol exposure

Abstract: Alcohol-induced liver disease is associated with unacceptable morbidity and mortality. When activated, Kupffer cells (KCs), the resident macrophages in the liver, release proinflammatory cytokine TNF-α, a key mediator of hepatic damage. Although chronic alcohol causes increase in norepinephrine (NE) release leading to hepatic dysfunction, the mechanism of NE-induced hepatic injury in chronic alcohol exposure has not been elucidated. This study was conducted to determine whether chronic alcohol exposure increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Studies have reported that chronic alcohol consumption induced liver injury associated with sympathetic hyperactivity, and implicated ROS in the pathogenesis of activation of the SNS, which may affect liver injury by modulating cellular oxidative damage . The major source of ROS is nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, an enzyme that can be activated during ethanol metabolism, leading to the production of superoxide anions (O – 2 ) in the liver.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have reported that chronic alcohol consumption induced liver injury associated with sympathetic hyperactivity, and implicated ROS in the pathogenesis of activation of the SNS, which may affect liver injury by modulating cellular oxidative damage . The major source of ROS is nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, an enzyme that can be activated during ethanol metabolism, leading to the production of superoxide anions (O – 2 ) in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the present study, 49-day ethanol consumption induced the oxidant-antioxidant balance shift toward oxidative damage predominance as evidenced by the increase in the production of 8-OHdG and the decrease in the cellular content of SOD-1 (Figs 3,4). Studies have reported that chronic alcohol consumption induced liver injury associated with sympathetic hyperactivity, 9,10,33 and implicated ROS in the pathogenesis of activation of the SNS, which may affect liver injury by modulating cellular oxidative damage. [34][35][36] The major source of ROS is nicotinamide adenine dinucleotide phosphate (NADPH) oxidase, an enzyme that can be activated during ethanol metabolism, leading to the production of superoxide anions (O -2) in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known about the role of DUSP1 in the liver [ 16 , 17 ]; in particular, the association of DUSP1 with HCV infection remains unclear. Also, the relationships between IFN and DUSP1-associated signaling have not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research indicates a chronic alcohol-induced, upregulated HPA axis system including corticotropinreleasing hormone (CRH) and noradrenergic signaling (Ajakaiye et al, 2011;Koob et al, 2004;Richardson, Lee, O'Dell, Koob, & Rivier, 2008;Sinha et al, 2009) in PLScircuit regions such as the amygdala with changes in related projections to the prefrontal cortex (Koob, 2009;Koob et al, 2004). Upregulation of these central stress pathways parallels changes in peripheral stress pathways as documented by higher basal adrenocorticotrophin (ACTH) and cortisol, blunted stress-induced ACTH and cortisol responses, and higher basal heart rate and lower heart rate variability in alcohol dependence (Adinoff, Iranmanesh, Veldhuis, & Fisher, 1998;Ingjaldsson, Laberg, & Thayer, 2003;Richardson et al, 2008;Shively et al, 2007;Sinha et al, 2009;Thayer, Hall, Sollers, & Fischer, 2006).…”
Section: Dysfunction In the Pls Circuit And Alcohol-relapse Riskmentioning
confidence: 96%